2007
DOI: 10.1089/apc.2007.0029
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Psychometric Outcomes of Facial Lipoatrophy Therapy: Forty-Eight–Week Observational, Nonrandomized Study

Abstract: The aim of this observational, prospective, nonrandomized study was to assess long-term psychometric outcomes of surgical treatment of HIV-related facial lipoatrophy. Two hundred ninety-nine participants (70.8% male) consecutively attending the Metabolic Clinic of Modena and Reggio Emilia University from November 2005 to July 2006, undergoing surgical interventions for HIV-related facial lipoatrophy were enrolled. Fifty-four (18.1%) underwent facial lipofilling, which consists of the harvesting of a small, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 18 publications
5
43
1
Order By: Relevance
“…In the current study, clinicians actively sought and palpated for nodules/papules, while others may have relied solely on patient report. Nodule onset times were consistent with those reported previously [13,35]; however, data on nodule duration are incomplete as many remained ongoing at study closure [9,13,17,33].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In the current study, clinicians actively sought and palpated for nodules/papules, while others may have relied solely on patient report. Nodule onset times were consistent with those reported previously [13,35]; however, data on nodule duration are incomplete as many remained ongoing at study closure [9,13,17,33].…”
Section: Discussionsupporting
confidence: 86%
“…These changes, while lower than the week 48 changes reported in some studies [9,11,17], are comparable to those reported in others [13,14]. However, cross-study comparisons of PLA efficacy for HIV facial lipoatrophy are problematic because of the heterogeneity of these studies.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…There are new and encouraging data on surgical treatment of facial lipoatrophy. 19 However, such treatment is usually not available in low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%